Sexual Stimulation Increases the Survival of New Cells in the Accessory Olfactory Bulb of the Male Rat - Unda, Nancy M.; Portillo, Wendy; Corona, Rebeca; Paredes, Raúl G. (Frontiers in Neuroscience, 2016)
Sexual behavior in rodents is modulated by the olfactory system. The olfactory bulb (OB) is a structure that undergoes continues neurogenesis in adulthood. We have previously shown that 15 days after males rats pace the sexual interaction and ejaculate 1 or 3 times, there is an increase in the density of new cells that reach the accessory olfactory bulb (AOB). The aim of the present study was to evaluate if sexual behavior in male rats increases the density of new neurons that survive 45 days after sexual behavior in the AOB and in the main OB (MOB). Male rats were randomly divided in four groups: 1) Control (Ctr), males without sexual interaction; 2) Exposed (Exp), males only exposed to a sexually receptive female; 3) No pacing (NP), males that mated in conditions in which the female paced the sexual interaction; 4) One ejaculation (1E), males that paced the sexual interaction with a receptive female and ejaculated once; and 5) Three ejaculations (3E), males that paced the sexual interaction and were allowed to ejaculate three times. All males were injected with the DNA synthesis marker 5-bromo-2-deoxyuridine (BrdU), and were tested in one of the above conditions. 45 days later they were sacrificed, and the OBs were processed to identify new cells and evaluate if they had differentiated into neurons. Our data indicate that males that ejaculated 3 times showed an increase in the density of new cells that survive in the posterior part of the granular cell layer of the AOB and have more new neurons that the control group. However, no significant differences were found in the percentage of new cells that differentiate into neurons. No significant increase in the density of new cells was observed in the MOB. Our data show that pacing the sexual interaction until 3 ejaculations increases the density of new cells and neurons in the granular layer of the AOB, confirming that sexual behavior induces long-lasting plastic changes in the OB.